Two-Stage Hydrothermal Synthesis of TiO₂ Nanotubes with Variation of Precursor Type for Diazinon Photodegradation - Tanti Haryati; Mustafid A’yun Assiddiq; Suwardiyanto Suwardiyanto; Novita Andarini; Yudi Aris Sulistiyo (Jurnal Kimia Sains dan Aplikasi, 2025)
TiO2 is commonly used as a photocatalyst for the photodegradation of harmful chemical compounds, such as diazinon. Its photocatalytic properties can be enhanced by fabricating it into nanotubes. TiO2 nanotube (TNTs) has a large surface area with good photon absorption and electron transport. This study aims to determine the effect of precursor type on the morphology, crystal structure, and photocatalytic activity of the resulting TNTs against diazinon. TNTs synthesis was carried out through a two-stage hydrothermal method using TiO2 micro powder precursors in anatase and rutile phases. The photocatalytic activity of TNTs was tested against diazinon photodegradation. The morphology of TNTs resulting from the first and second hydrothermal processes was fiber-shaped for anatase TNP precursor (TNPa) and rutile TNP precursor (TNPr). TEM characterization showed that the TNT particles were tubular with an outer diameter of 2.27-10.92 nm and an inner diameter of 1.10-4.2 nm. Some impurities, such as sodium titanate and hydrogen titanate, still appear in the diffraction patterns of TNTa and TNTr. The TNTr photocatalyst underwent crystal phase transformation into anatase, which was compared with the JCPDS data. The percentage of degradation for TNTa photocatalyst is slightly greater than TNTr, reaching 85.9% and 82.4%, respectively.